PERAN PENYULUHAN DENGAN MENGGUNAKAN LEAFLET TERHADAP PERUBAHAN PENGETAHUAN DAN SIKAP IBU BALITA GIZI KURANG - Salimar Salimar; Sri Muljati; Agus Triwinarto; Rousmala Dewi (Persagi, 2009)
ABSTRACT Background: Nutrition extension is one of the approach efforts to increase knowledge in order to gain good behavior. Through this extension, we expected mother of under five years child would understood and comprehended as well as had a willing and could implement what she was advised, so that she could took care of under five years child with underweight nutrition to become better nutrition. Purpose: To study about the changing of knowledge and attitude of mother with undernourished of under-five years child after got intervention of extension for 3 months of between two groups got leaflet and didn't get leaflet. Methods: This applied research applied quasi experiment research design. Population is mother having undernourished of under five years child and mother age ranges from 18-45 years, totally 176 samples. Group of treatment got extension package for 3 months and given leaflet to be studied in house. Group of control was participated extension package for 3 months, but they weren’t given leaflet, and leaflet was given after this research completed. Results: After followed extension package during 3 months, samples showed improvement for mother’s knowledge as 11.4% in group of treatment and 10.4% in group of control. Statististically by using Chi quadrate test, there were a significance difference (p=0.00) for mother’s knowledge before and after research in both group of research. There is a changing for mother’s attitude in group of treatment as 28.1% and 16.1% in group of control. By using chi square test we found significance difference (p=0,021) on mother’s attitude in group of treatment before and after extension for 3 month, while in group of control there was no significance difference ( p=0.187). Conclusions: Leaflet is one of the supporting facilities which applicable to change knowledge and attitude of mother. There is no difference of mother’s motivation in participating this research. The role of husband and parents were big enough in two groups of research in the treatment of nutrition undernourished child, especially in parenting and decision making in child recovery from sickness. Recommendation: This research need to be continued to study about extension impact to on mother’s behavior while taking care child. Extension for husbands needs to be done to involve them in child parenting and treatment process to quicken the improvement of nutrition of under-five years child. [Penel Gizi Makan 2009, 32(2): 119-128] Key word: Leaflet, extension, undernourished, knowledge, attitude.